Disparities in Internet Medical Service Utilization Among Patients in Post–COVID-19 China: Cross-Sectional Study of Data From Provincial Field and National Online Surveys - Zhenyu Sun; Xi Chen; Dongfu Qian (Journal of Medical Internet Research)
Abstract BackgroundInternet medical services (IMS) expanded rapidly in China during the COVID-19 pandemic. Unfortunately, disparities in internet medical services utilization (IMSU) have marginalized disadvantaged groups of Chinese patients from digital health benefits. The extent and nature of these disparities remain poorly understood, with no research comprehensively addressing how unfavorable predictors, including demographic, socioeconomic, and health-related factors, shape IMSU status, patterns, and preferences in China after the COVID-19 pandemic. ObjectiveThis study aims to gain a deeper understanding of the disparities and unfavorable predictors that limit IMSU among Chinese adult patients following the COVID-19 pandemic, providing key reference points for advancing equitable IMSU. MethodsThis cross-sectional study used a triangular approach, combining data from a provincial field survey conducted in July 2023 and a national online survey conducted in March 2024. Participants were Chinese adult outpatients aged 18 years or older. Descriptive and comparative analyses were used to examine disparities in IMSU status, patterns, and preferences across different demographic, socioeconomic, and health status–related factors. Binary logistic regression models were applied to assess the associations between unfavorable predictors (constructed from selected demographic, socioeconomic, and health status–related factors) and IMSU status, patterns, and preferences. ResultsOf the 2011 eligible participants in the Jiangsu provincial field survey, 787 (39.13%) reported using IMS at least once in the previous 12 months. Among the 1611 eligible participants in the national online survey, all reported accessing IMS during the same period; however, only 481 (29.86%) reported high-frequency use (defined as usage in the third quartile or above, ie, ≥6 times). Overall, participants with unfavorable predictors were less likely to engage in IMSU, deep IMS were used less frequently than shallow IMS, and participants with 6 or more cumulative unfavorable predictors had the lowest total of IMSU preference score (mean 48.98 and 57.37 in the provincial field and national online surveys, respectively). Based on combined data from the provincial field and national online surveys, significantly negative associations were observed between unfavorable predictors and IMSU status, patterns, and preferences. In particular, participants aged 60 years or above (odds ratio [OR] 0.40, 95% CI 0.25‐0.63, PPPPP ConclusionsWidespread disparities in IMSU status, patterns, and preferences persisted among Chinese adult patients after the COVID-19 pandemic. More pro-disadvantaged patient policies may be warranted to narrow these disparities in IMSU, such as reimbursement for IMSU, to promote digital health equity in China.